2012
DOI: 10.1007/s10459-012-9375-y
|View full text |Cite
|
Sign up to set email alerts
|

How much of the paediatric core curriculum do medical students remember?

Abstract: Few educational studies have investigated how well information learned by medical students is retained over time. The primary aim of this study was to investigate how much of the paediatric core curriculum undergraduates remembered a year after originally passing their paediatrics examination. In addition, we looked at whether students' repeat performance is related to their approach to learning. Medical students were presented with 8 out of a possible 46 core curriculum short answer questions (Mark 1). A year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
1
23
1
Order By: Relevance
“…The results of Sullivan et al [23] suggest this does not play a major role: students in this study performed similar on questions they had seen before and new questions. Incidentally, our study reinforces this conclusion: in one extended matching question (from Healthy & Diseased Cells) students had to match five one-sentence descriptions of different diseases with the names of these diseases.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The results of Sullivan et al [23] suggest this does not play a major role: students in this study performed similar on questions they had seen before and new questions. Incidentally, our study reinforces this conclusion: in one extended matching question (from Healthy & Diseased Cells) students had to match five one-sentence descriptions of different diseases with the names of these diseases.…”
Section: Discussionsupporting
confidence: 44%
“…For example, Arzi et al [22] found approximately 53% retention of knowledge of the Periodic Table in high school students after a retention interval of 1 year. Sullivan et al [23] report a reduction of approximately 51% of paediatric knowledge in final year medical students after a retention interval of 1 year. D'Eon [24] tested second year medical students after 10-11 months and found considerably more retention of physiology and immunology knowledge (80%) than neuroanatomy knowledge (47.5%).…”
Section: Discussionmentioning
confidence: 99%
“…9,18 As research into the reliability and validity of the Biggs' R-SPQ-2F has been fairly extensive, this validated instrument was anticipated to serve as a reasonable way to investigate the students' approaches to learning in our study. 18,[19][20][21] In order to evaluate the impact of the flipped examination model and assess any possible changes in the students' attitudes and perceptions of their learning process, the same questionnaire was administered both before and after the . According to the scoring system provided by Biggs, total DA and SA scores were calculated as the sum of all DA scale items and SA scale items, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, various ways to calculate retention and decrement of performance have been described. We decided to define decline as the absolute difference in percent scores as this method is widely used [25,26]. However, analysing our data using alternative formulae and adjusting for performance in the entry exam [27] did not substantially alter our results (data not shown).…”
Section: Strengths and Limitationsmentioning
confidence: 95%